Multicolour-metallicity relations from globular clusters in NGC 4486 (M87) - Forte, Juan Carlos (2013)
We present Gemini griz' photometry for 521 globular cluster (GC) candidates in a 5.5 × 5.5 arcmin2 field centred 3.8 arcmin to the south and 0.9arcmin to the west of the centre of the giant elliptical galaxy NGC 4486. All these objects have previously published (C - T1) photometry. We also present new (C - T1) photometry for 338 globulars, within 1.7 arcmin in galactocentric radius, which have (g - z) colours in the photometric system adopted by the Virgo Cluster Survey of the Advanced Camera for Surveys of the Hubble Space Telescope (HST). These photometric data are used to define a self-consistent multicolour grid (avoiding polynomial fits) and preliminarily calibrated in terms of two chemical abundance scales. The resulting multicolour colour-chemical abundance relations are used to test GC chemical abundance distributions. This is accomplished by modelling the 10 GC colour histograms that can be defined in terms of the Cgriz' bands. Our results suggest that the best fit to the GC observed colour histograms is consistent with a genuinely bimodal chemical abundance distribution NGC(Z). On the other side, each ('blue' and 'red') GC subpopulation follows a distinct colour-colour relation.